Local Delivery of Chitosan/VEGF siRNA Nanoplexes Reduces Angiogenesis and Growth of Breast Cancer In Vivo - EREN, FATİH; KABASAKAL, LEVENT; ÖZKAN YENAL, NAZİYE (MARY ANN LIEBERT, INC, 2012)
Vascular endothelial growth factor (VEGF) is the important angiogenic factor associated with tumor growth and metastasis in a wide variety of solid tumors. The aim of this study is to investigate the tumor suppressive effect of chitosan/small interfering RNA (siRNA)-VEGF nanoplexes in the rat breast cancer model. Chitosan/siRNA nanoplexes (siVEGF-A, siVEGFR-1, siVEGFR-2) and NRP-1 were prepared in a 15 to1 ratio and injected (intratumorally) into the breast-tumor-bearing Sprague-Dawley rats. Tumor volumes were measured during 21 days. To investigate the effect of chitosan/siRNA nanoplexes on VEGF expression in tumors, VEGF was analyzed with immunohistochemistry and western blotting. The mRNA levels of VEGF in tumor samples were determined with real-time PCR (RT-PCR). After siRNA treatment, a marked reduction in tumor volumes was measured in complex-injected rats (97%). Free siRNA injection showed lower tumor inhibition. Reduction of VEGF protein was also shown with western blotting and immunohistochemistry. Similar results were obtained with RT-PCR also. These results indicate that the chitosan/siRNA targeting to VEGF nanoplexes have a remarkably suppressive effect on VEGF expression and tumor volume in breast cancer model of rats.
Keywords: POLYELECTROLYTE COMPLEX MICELLES; VEGF SIRNA; TUMOR ANGIOGENESIS; RNA INTERFERENCE; TARGETING VEGF; GENE-THERAPY; CELL-LINES; EXPRESSION; NANOPARTICLE; THERAPEUTICS